2016
DOI: 10.1155/2016/4698462
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pyelonephritis with Bacteremia Caused byEnterococcus hirae: A Rare Infection in Humans

Abstract: Enterococci are one of the usual residents of the microflora in humans. In the last decade this genus has been reported as the third most common cause of bacteremia. We present the case of a 78-year-old female who was admitted to the emergency room because of nausea, lipothymia, and weakness. She was diagnosed with a pyelonephritis with bacteremia, with the isolation in blood and urine cultures of Escherichia coli and Enterococcus hirae. This last microorganism is a rarely isolated pathogen in humans. Currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…According to the plans, ampicillin-based therapy with concomitant gentamicin or vancomycin is widely used as a treatment of choice for enterococcal infections. Other cases of E. hirae-related pyelonephritis (Table 1) [4,5,[7][8][9][10], except for our case report, showed an antibiotic duration of 10 to 14 days, and the antibiotics of choice were ampicillin, ampicillin/ sulbactam, or amoxicillin. In some areas, our report differed from that of previous cases, predominantly changing the antibiotics from ciprofloxacin to ampicillin/sulbactam.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…According to the plans, ampicillin-based therapy with concomitant gentamicin or vancomycin is widely used as a treatment of choice for enterococcal infections. Other cases of E. hirae-related pyelonephritis (Table 1) [4,5,[7][8][9][10], except for our case report, showed an antibiotic duration of 10 to 14 days, and the antibiotics of choice were ampicillin, ampicillin/ sulbactam, or amoxicillin. In some areas, our report differed from that of previous cases, predominantly changing the antibiotics from ciprofloxacin to ampicillin/sulbactam.…”
Section: Discussionmentioning
confidence: 68%
“…Except in cases of urinary tract infections, E. hirae infections were treated using cefmetazole (bacteremia with cholangitis) [7]; ampicillin combination therapy comprising gentamicin and levofloxacin (spondylodiscitis) [1]; vancomycin (hemodialysis with bacteremia); three combination regimens with either vancomycin and gentamicin, amoxicillin and gentamicin, or ampicillin and rifampin (infective endocarditis); ampicillin combination therapy comprising piperacillin/tazobactam and levofloxacin (splenic abscess), and ampicillin (peritonitis). Each of the treatment had an average therapeutic duration of 2 weeks, with a maximum duration of 8 weeks [8]. Since E. hirae has low virulence, the pathogen can presumably be treated using antibiotic monotherapy in cases of non-invasive infections, such as urinary tract infections [9].…”
Section: Discussionmentioning
confidence: 99%
“…8 Many studies showed that the transmission of E. hirae from animal to human and human to animal is possible. 9,10 The incident number of E. hirae infection is the lowest, 1-3% of Enterococci infection. E. hirae is bacteremia, and associated to kidney diseases, endocarditis, spondylodiscitis, pyelonephritis, and cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although Enterococcus faecalis and Enterococcus faecium cause the majority of reported nosocomial infections at a frequency of 90–95% and 5–10%, respectively (Ceci et al., ; Kristich, Rice, & Arias, ), Enterococcus hirae have historically been associated with pathological conditions in animals (Ghosh et al., ; Sim et al., ). However, in recent decades, many cases of human infection with E. hirae have been reported and this bacterium has been implicated as a source of severe and life‐threatening illness, such as septicemia, endocarditis, and urinary tract infections (Alfouzan et al., ; Anghinah et al., ; Bourafa, Loucif, Boutefnouchet, & Rolain, ; Dicpinigaitis, De Aguirre, & Divito, ; Kim et al., ; Paosinho et al., ; Savini et al., ). Moreover, the pathogenic potential of E. hirae may be underappreciated due to misidentification.…”
Section: Introductionmentioning
confidence: 99%